Co-design of the neurodevelopment assessment scale - Wong, Tsz Ying; Azim, Syeda Ishra; Lam-Cassettari, Christa; Lin, Ping-I.; Mendoza Diaz, Antonio; Montgomery, Alicia; Masi, Anne; Mallitt, Kylie-Ann; Whitehouse, Andrew; Dadds, Mark R.; Eapen, Valsamma (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionNeurodevelopmental disorders (NDDs) have high comorbidity rates and shared etiology. Nevertheless, NDD assessment is diagnosis-driven and focuses on symptom profiles of individual disorders, which hinders diagnosis and treatment. There is also no evidence-based, standardized transdiagnostic approach currently available to provide a full clinical picture of individuals with NDDs. The pressing need for transdiagnostic assessment led to the development of the Neurodevelopment Assessment Scale (NAS).MethodsThis paper describes the co-design process used in the development of NAS prototype with stakeholders including individuals with NDDs, parents of children with NDDs, and health professionals.Results and discussionResults indicated stakeholder consensus that NAS would be useful for NDD assessment, and included recommendations for fine-tuning the way some questions were asked (e.g., child's diagnoses), question flow (e.g., branching logic), and the language and presentation of the prototype (e.g., readability). Stakeholders also suggested the administration protocol should be flexible using electronic, face-to-face, online formats etc.